Menilai Kembali Kapasitas Pajak Daerah: Mampukah Menggeser Sektor Terbelakang Menjadi Sektor Maju? - Nugrahajati, Oki Sakti; Wahyudi, Setyo Tri; Riza, Ahmad Ibnu; Hakim, Annisa Nurul (UI Scholars Hub, 2026)
Tulungagung Regency’s Locally Generated Revenue (PAD) remains concentrated in three main types of taxes, while levies contribute less than optimally. This study aims to analyze the potential and performance of regional taxes and levies as instruments of fiscal independence in Tulungagung Regency using overlay analysis. The analysis shows that several taxes with low contributions have experienced significant growth, indicating policy space for expanding the revenue base. This finding implies that the overlay analysis approach can guide the determination of more precise and contextual fiscal strategies, as well as contribute to the development of a regional fiscal evaluation framework and the design of an adaptive fiscal system in the era of fiscal decentralization.